Financial Accounting Financial Accounting Strategy for Sustainable Development of MSMEs in Indonesia: MSMEs, Financial Accounting, Digital Transformation - Dea Haritiantari; Hamzani, Umiaty; Desyana, Gita; Permata Indah, Djunita (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, but face complex challenges in financial accounting management. This research aims to analyze financial accounting strategies for sustainable development of MSMEs in Indonesia. The research method employs a qualitative library research approach by exploring various literature, documents, and related research. The research results reveal that the majority of MSMEs still use traditional accounting systems with limited digital infrastructure and literacy. The study identifies four critical dimensions in financial accounting transformation: digital technology, human resource development, regulatory frameworks, and sustainable empowerment strategies. The developed strategy model offers an adaptive approach capable of accommodating the diversity of MSME characteristics. Findings indicate that digital technology integration, continuous training, and ecosystem support can significantly improve MSME financial performance. The research recommends building integrated digital platforms, comprehensive incentive policies, and multi-stakeholder collaboration to drive MSME financial accounting transformation.